AN ANALYSIS OF MALE AND FEMALE STUDENTS’ STRATEGIES IN LEARNING SPEAKING SKILLS IN POST PANDEMIC CONTEXT - Fitriani Fitriani; Ismail Sangkala; Ika Sastrawati (Journal of Language Testing and Assessment, 2022)
The aimed of this research was to find out the strategies of male and female students in learning speaking skills during the post pandemic. The method used in this research was qualitative method in the type of phenomenological research. This research used a semi-structure interview as instrument to collect the data. The subjects in this research were 4th semester students of English Education Department, at Universitas Muhammadiyah Makassar. The research subjects were 10 students which consist of 5 female students and 5 male students. This research used purposive sampling technique. The results of this research showed that male and female students used all types of strategies; memory strategies, cognitive strategies, compensation strategies, metacognitive strategies, affective strategies, and social strategies in learning speaking during the post-pandemic. The difference only lays the number of male and female students in using the methods of each group strategies and the difference in the method used in the group strategies by male and female students. Female students used each group learning strategies more than male students. Most of female students used memory strategies, cognitive strategies, compensation strategies, metacognitive strategies and social strategies. While most of male students used memory strategies, cognitive strategies, compensation strategies and metacognitive strategies.